2009
DOI: 10.1177/0265407509345649
|View full text |Cite
|
Sign up to set email alerts
|

Family communication patterns as mediators of communication competence in the parent—child relationship

Abstract: In this study we examined family conversation and conformity orientations as mediators of the association between young adults' perceptions of their parents' communication competence and their own self-reported communication competence. Participants included 417 young adult children from the United States. Although measurement invariance was established for both sons and daughters, separate models were tested to account for significant differences in correlations between both groups. For daughters, the associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
44
4
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 49 publications
6
44
4
4
Order By: Relevance
“…Basically, previous research has generally found strong connections between conversation orientation and individual traits of competence (e.g., Keaten & Kelly, 2008), and this study adds to the general literature regarding the importance of family conversation in the development of a competent, healthy individual. However, the current study stands in contrast to several previous studies that found no relationship between conformity orientation and individual traits of either emotional intelligence or a more general trait of communication competence (Keaten & Kelly, 2008;Schrodt et al, 2009). Future research should continue to examine the potential links, both positive and negative, between family conformity and individual development.…”
Section: Main Conclusioncontrasting
confidence: 94%
“…Basically, previous research has generally found strong connections between conversation orientation and individual traits of competence (e.g., Keaten & Kelly, 2008), and this study adds to the general literature regarding the importance of family conversation in the development of a competent, healthy individual. However, the current study stands in contrast to several previous studies that found no relationship between conformity orientation and individual traits of either emotional intelligence or a more general trait of communication competence (Keaten & Kelly, 2008;Schrodt et al, 2009). Future research should continue to examine the potential links, both positive and negative, between family conformity and individual development.…”
Section: Main Conclusioncontrasting
confidence: 94%
“…Intergenerational transmission, as a process in which an earlier generation psychologically influences the parenting attitudes and behavior of the next generation, has been extensively confirmed in the theoretical, empirical, and clinical literature (e.g., Chen, Liu, & Kaplan, 2008;Gitelson & McDermott, 2006;Goodnow, 2005;Schrodt et al, 2009).…”
Section: Intergenerational Transmission and Intergenerational Gapsmentioning
confidence: 95%
“…The methods used in other parent–child programmes were regarded as useful in stimulating positive parent–adolescent communication, such as derived from Faber and Mazlish (2004), authors of How to talk so teens will listen, and how to listen so teens will talk , and Non-Violent Communication (NVC) by Marshall Rosenberg (2003). Central to such approaches are the focus on tuning into the child’s emotional state, without aiming to consult or change it directly, and to support the child in communicating their current emotional state (Schrodt et al 2009). In the group, a combination of such approaches was used to explore fictional as well as real-life situations of parents and children. …”
Section: Introductionmentioning
confidence: 99%